NATURAL COMPOUNDS FROM DJIBOUTIAN MEDICINAL PLANTS AS INHIBITORS OF COVID-19 BY IN SILICO INVESTIGATIONS - ELMI, ABDIRAHMAN; SAYEM, S. AL-JAWAD; AHMED, MOHAMED; ABDOUL-LATIF, FATOUMA (International Journal of Current Pharmaceutical Research, 2020)
Objective: The new coronavirus type SARS-Cov 2 (severe acute respiratory syndrome), which appeared in autumn 2019 in China, became a global pandemic in a few months. In this work, we looked for the potential anti SARS-Cov 2 of the compounds isolated from three Djiboutian medicinal plants, namely Acacia seyal, Cymbopogon commutatus, and Indigofera caerulea. Methods: We carried out a molecular docking with nine biomolecules, β-Sitosterol, Quercetin, Catechin, Lupeol, Rutin, Kaempferol, Gallic acid, Piperitone and Limonene on three target sites which are SARS-CoV-2 main protease (Mp), SARS-CoV-2 receptor-binding domain (RBD) and human furin protease. These targets are chosen because of their role in the process of penetration of the virus into human cells and its multiplication. Moreover, the predictions of pharmacokinetic parameters as well as toxicological properties have been determined using an online bioinformatics tool named SwissADME and AdmetSAR respectively. Results: The phenolic compounds have a very good affinity on these three target sites with binding energies of up to-9.098 kcal/mol for rutin on SARS-CoV-2 Mp, much better than the two reference drugs hydroxychloroquine (-5.816 kcal/mol) and remdesivir (-7.194 kcal/mol). Except for β-Sitosterol, the tested biomolecules have weak toxicity. Conclusion: These natural compounds can be used against covid 19 pending In vitro and In vivo evaluations.